Temporal and morphological impact of pressure overload in transgenic FHC mice - Chen, Hao; Hwang, Hyosook; McKee, Laurel A.; Perez, Jessica N.; Regan, Jessica A.; Constantopoulos, Eleni; LaFleur, Bonnie; Konhilas, John P. (Frontiers in Physiology, 2013)
Although familial hypertrophic cardiomyopathy (FHC) is characterized as cardiac disease in the absence of overt stressors, disease penetrance and pathological progression largely depend on modifying factors. Accordingly, pressure overload by transverse aortic constriction (TAC) was induced in 2 month-old, male mice with and without a FHC (R403Q) mutation in α-myosin heavy chain. A significantly greater number of FHC mice (8) than wild-type (WT) mice (5) died during the 9-week study period. TAC induced a significant increase in cardiac mass whether measured at 2 or 9 weeks post-TAC in both WT and FHC mice, albeit to a different extent. However, the temporal and morphological trajectory of ventricular remodeling was impacted by the FHC transgene. Both WT and FHC hearts responded to TAC with an early (2 weeks post-TAC) and significant augmentation of the relative wall thickness (RWT) indicative of concentric hypertrophy. By 9 weeks post-TAC, RWT decreased in WT hearts (eccentric hypertrophy) but remained elevated in FHC hearts. WT hearts following TAC demonstrated enhanced cardiac function as measured by the end-systolic pressure-volume relationship, pre-load recruitable stroke work, and myocardial relaxation indicative of compensatory hypertrophy. Similarly, TAC induced differential histological and cellular remodeling; TAC reduced expression of the sarcoplasmic reticulum Ca2+-ATPase (2a) (SERCA2a; 2 and 9 weeks) and phospholamban (PLN; 2 weeks) but increased PLN phosphorylation (2 weeks) and β-myosin heavy chain (β-MyHC; 9 weeks) in WT hearts. FHC-TAC hearts showed increased β-MyHC (2 and 9 weeks) and a late (9 weeks) decrease in PLN expression concomitant with a significant increase in PLN phosphorylation. We conclude that FHC hearts respond to TAC-induced pressure overload with increased premature death, severe concentric hypertrophy, and a differential ability to undergo morphological, functional or cellular remodeling compared to WT hearts.